Membangun Keimanan Anak melalui Pembelajaran Hari Akhir di Sekolah Dasar - Ratna Sholihah; Aisyah Hana Robbani; Oktavia Rahmadani; Roza Andini; Mahmud Alfayed; Wismanto Wismanto (Jurnal Budi Pekerti Agama Islam, 2025)
Religious education plays a crucial role in shaping the faith and character of children from an early age. One of the important subjects in Islamic religious education at the elementary school level is the teaching of the concept of the Day of Judgment. This teaching is expected to strengthen students' faith and shape their behavior in accordance with religious teachings. This study aims to analyze how the teaching of the Day of Judgment in elementary schools can build children's faith. The research method used is a qualitative approach with a case study design. Data was collected through observation, interviews with teachers and students, and documentation. The results of the study indicate that teaching about the Day of Judgment enhances students' understanding of the afterlife and the importance of good deeds. Varied teaching methods, such as storytelling, discussions, and reflective activities, proved effective in helping students understand these abstract concepts. This learning also has a positive impact on students' attitudes and behaviors, such as increased discipline, honesty, and empathy toward others. However, there are challenges in teaching abstract concepts to children that need to be addressed with more creative and contextual approaches.